SPEED CONTROL IN NUMERIC CONTROLLED SYSTEMS - Dimovski, Igor; Samak, Samoil; Cvetkoska, Dijana; Trompeska, Mirjana; Kochoski, Filip (Matematichki Bilten, 2015)
In order to achieve higher speed (higher productivity at the same time), the modern way of managing numerical controlled systems includes Look Ahead algorithms with strong mathematical background. The purpose of these algorithms is generating a speed profile with which the tool will move along the programmed movement path. In this article will be described a method for speed profile generating whereby we will use numerical methods for differential computing, spline interpolation/ approximation and linear programming. For testing and view of the generated speed profiles we will use the programming package MATLAB.